Emigrant Literature – The Object Of Strict Soviet Surveillance - Mikaberidze, Maia (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2016)
The Soviet Government considered the emigrant literature as a strong ideological weapon having an adverse impact on Soviet people worldview. That was why to bring the emigrant literature to the Soviet Union first restricted and lately banned. Among the forbidden newspapers and magazines were the Georgian emigrant publications. Instead, it was decided to publish a reference book of the most important publications. In the years of 1927-1933 Tbilisi was issued in Russian “Foreign White Press Bulletin ( Transcaucasia ) ”Bulletin of Foreign Printed Materials ”( about Transcaucasia)”, which included the reviews and paragraphs of not only the Georgian emigrant literature but the Transcaucasian publications as well. Due to materials printed in these bulletins the Soviet Government knew about the emigrant circles, their point of views and goals. Thorough analysis of emigrant literature gave a possibility to the Soviet Government to react efficiently and undertake relevant actions. The Bulletin was strictly confidential and it was a sample of totalitarian regime repressive politics.